Constraints and potentials of handicraft industry in underdeveloped region of Malaysia - Redzuan, Ma'rof; Aref, Fariborz (Academic Journals, 2011)
The main purpose of this study is to identify the constraints and potentials faced by handicraft industry in a peripheral and underdeveloped region of Malaysia. The study was carried out in the Districts of Kota Bharu and Tumpat in the State of Kelantan, Malaysia, and targeted the entrepreneurs and workers in the silverware and batik handicraft enterprises, and also villagers who were not directly involved in these industries. The study is based upon qualitative analyses of material derived from field-work in several villages in the study area. It seeks to place handicrafts production in Kelantan within the broader theoretical context of rural industrialization and the development of traditional and peripheral rural areas.